The influence of the Greek novel on the Life and Miracles of Saint Thecla - Narro, Ángel, 1985- (2016)
The Life and Miracles of Saint Thecla, a 5th-century hagiographical work, feature many elements recalling the ancient novel. Even if the first part of the text, the Life, must be considered a novel itself due to its dependence on the model of the Acts of Paul and Thecla, some novelistic motifs - especially the use of descriptions, digressions and first-person narrations − appear throughout the whole text. In addition, we also examine the textual evidence of the influence of the ancient novel on this hagiographical text through the analysis of some lexical details which suggest the reading of the ancient novels. The hagiographer uses these elements to rewrite in same cases the original scene of the Acts of Paul and Thecla or to evoke in other scenes the universe of the ancient novel in order to delight his readers.
Keywords: Literatura griega; Religiosas; Milagros; Hagiografía